Evaluation of serological assays for intra vitam diagnosis of bovine tuberculosis in water buffalo (Bubalus bubalis) - Giovannozzi, Sara; Martucciello, Alessandra; Rodríguez, Mercedes Domínguez; Iruela, Inmaculada Moreno; Boifava, Mery; Schiavo, Lorena; Viscito, Anna; Parisio, Giovanni; Vitale, Nicoletta; Bezos, Javier; De Carlo, Esterina; Boniotti, Maria Beatrice (Frontiers in Microbiology, 2025)
IntroductionBovine tuberculosis (TB) in water buffalo (Bubalus bubalis) is primarily diagnosed using intra vitam tests, as the intradermal tuberculin test (IDT) and the interferon-gamma release assay (IGRA), both of which detect cell-mediated immunity (CMI). However, a subset of infected animals fails to mount a detectable CMI response, posing a significant risk of undetected transmission. Serological tests assessing the humoral immune response could provide a valuable complementary tool for identifying infected animals that escape detection through traditional CMI-based assays.MethodsThis study analyzed 895 serum samples from water buffaloes, including 393 from TB-free herds and 502 from TB-infected herds. Animals from TB-free herds were tested using IDT and an ELISA assay, whereas those from infected herds were also tested using IGRA. We developed an ELISA assay targeting MPB70, MPB83, ESAT6, CFP10, PPDB, and P22 antigens to investigate the role of the humoral response in TB diagnosis.Results and discussionThe ELISA showed a specificity of 98.2%. However, sensitivity differed based on the antigen used: among the most reactive proteins, sensitivity was 67.5% for MPB70, 69.8% for P22, and 74.4% for PPDB. Moreover, approximately 70% of samples with discordant IDT and IGRA results, as well as those with positive IDT but inconclusive IGRA results, tested positive by serology, highlighting the potential of antibody-based detection to improve TB diagnosis in buffaloes. Our findings suggest that integrating serological testing with standard diagnostic methods could enhance the detection of infected animals, ultimately contributing to better TB control in buffalo populations.